PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIK PESERTA DIDIK SMP MELALUI MODEL PEMBELAJARAN CONNECTED MATHEMATICS PROJECT - Desi Susanti; Yayu Laila Sulastri (Universitas Islam Nusantara, 2020)
This research is motivated by the low mathematical problem solving ability experienced by students so that a relevant learning model is needed to solve the problem, one of them is the Connected Mathematics Project model. Therefore, the purpose of this research is to find out the improvement of students' mathematical problem solving abilities through the Connected Mathematics Project learning model and how students respond to this learning model. This study was a quasi-experimental study in one of the junior high schools in Bandung district in 2018/2019. The samples in this study were students of class VII A and VII E. The instruments used in this study were tests of mathematical problem solving abilities, student questionnaires and observation sheets. Data obtained from the results of tests of mathematical problem-solving abilities were analyzed quantitatively, while data obtained from questionnaires and observation sheets were analyzed qualitatively. The results of the research conducted showed that increasing the mathematical problem solving ability of students who use the Connected Mathematics Project learning model is better than students who use the Discovery Learning learning model and responds very well to the application of the Connected Mathematics Project model. Empirically it can be seen that the mathematical problem solving ability of students who obtain learning with the Connected Mathematics Project learning model is better than students who obtain learning with the Discovery Learning model and positive student responses.